Edge computing and capability oriented architecture - Bai, Haishi; Scholl, Boris (CRC Press, Taylor & Francis Group, 2022)
Fueled by ubiquitous computing ambitions, the edge is at the center of confluence of many emergent technological trends such as hardware-rooted trust and code integrity, 5G, data privacy and sovereignty, block chains and distributed ledgers, ubiquitous sensors and drones, autonomous systems, real time and stream processing. Hardware and software pattern maturity have reached a tipping point so that scenarios like smart-homes, smart-factories, smart-buildings, smart-cities, smart-grids, smart-cars, smart-highways are in reach of becoming reality.